2021
DOI: 10.1016/j.imr.2020.100706
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns of herbal medicine for menopausal disorders in major Korean medicine hospitals: A multicenter retrospective study

Abstract: Background This study aimed to obtain the symptom, prescription and therapeutic patterns for the treatment of patients with menopausal syndrome in major Korean medicine (KM) hospitals. Methods We used a retrospective chart review of climacteric disorder and postmenopausal syndrome patients by examining medical records (ICD-10, menopausal and female climacteric states: N95.1, Menopausal and perimenopausal disorder, unspecified: N95.9) from eight university KM hospitals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Herbal medicine (HM) is widely used for women’s healthcare [ 6 , 7 , 8 , 9 , 10 , 11 ]. Korean medicine (KM) is the conventional medicine used in South Korea, and most treatments are covered by the national health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal medicine (HM) is widely used for women’s healthcare [ 6 , 7 , 8 , 9 , 10 , 11 ]. Korean medicine (KM) is the conventional medicine used in South Korea, and most treatments are covered by the national health insurance system.…”
Section: Introductionmentioning
confidence: 99%
“…Xiaoyao-san (XYS; also called Soyo-san in traditional Korean medicine and Shoyo-san in Kampo medicine) is a traditional herbal formula composed of eight botanical drugs: Glycyrrhizae radix et rhizoma , Angelicae sinensis radix , Poria cocos , Paeoniae radix alba , Atractylodis macrocephalae rhizoma , Bupleuri radix , Menthae herba , and Zingiberis rhizoma recens ( Qin et al, 2009 ). XYS is one of the representative prescriptions traditionally used for gynecological diseases such as menopausal symptoms ( Chen et al, 2011 ; Lee et al, 2021 ). Some laboratory studies have demonstrated estrogen- ( Hu et al, 2022 ) and antidepressant-like effects of XYS ( Dai et al, 2010 ; Yuan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ekstrak MeOH rimpang kunir putih menunjukkan efek sitotoksik terhadap sel AGS kanker lambung menggunakan uji viabilitas sel MTT. Senyawa Kurkumenol, 4,8-dioxo-6β-methoxy-7α,11-epoxycarabrane dan zedoarofuran diidentifikasi sebagai komponen sitotoksik utama dalam rimpang kunir putih(55). Dalam penelitian lain juga melaporkan bahwa minyak atsiri yang diperoleh dari kunir putih memiliki efek sitotoksik yang efisien pada sel karsinoma paru non-sel kecil (NSCLC) dan menyebabkan apoptosis sel.…”
unclassified